2018
DOI: 10.1159/000487700
|View full text |Cite
|
Sign up to set email alerts
|

Is Human Papilloma Virus Associated with Breast Cancer? A Review of the Molecular Evidence

Abstract: Background: Although the association of human papillomavirus (HPV) with many cancers is well established, the involvement of HPV in breast cancer remains controversial. The purpose of this study is to perform a comprehensive review of the results and methods used to demonstrate that HPV markers are present in human breast cancer, and how well these studies fulfil the criteria for proving the viral etiology of a cancer. Study Design: We conducted a search for molecular studies published until November 2016 that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 70 publications
1
14
0
Order By: Relevance
“…Long-term virus persistence and the participation of other cofactors are needed to increase the risk of cancer progression [28,29]. In support of this statement, our data may suggest that the detection of HPV infection in normal breast specimens is expected to be an early event at the time of diagnosis, followed by progressive and cumulative changes over the years, similar to cervical carcinogenesis [22].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Long-term virus persistence and the participation of other cofactors are needed to increase the risk of cancer progression [28,29]. In support of this statement, our data may suggest that the detection of HPV infection in normal breast specimens is expected to be an early event at the time of diagnosis, followed by progressive and cumulative changes over the years, similar to cervical carcinogenesis [22].…”
Section: Discussionsupporting
confidence: 55%
“…HPV infection also causes direct effects through the expression of viral oncoproteins that influence carcinogenic mechanisms and its oncogenic role is well-known in cervical cancer [21]. It has recently been suggested that the HPV oncogenicity in breast tissue could be similar to cervical carcinogenesis, in which viral infection could be an early event, followed by cumulative changes over the chronic viral infection [22].…”
Section: Discussionmentioning
confidence: 99%
“…HPV was detected in the blood of a subset of sexually naïve children with hemophilia who had received multiple transfusions [1]. HPV sequences are sometimes found in tumours of internal organs such as the stomach, prostate, breast, colon, bladder, esophagus, and lung [3,9,11,45–49]. We asked whether these observations could be due to transmission of the virus through the blood.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these children were hemophiliacs who had contracted HIV through contaminated transfusions. HPV has been detected in malignant tissues, including those of the head and neck [2], esophagus [3], lung [4], colorectum [5,6], prostate [7,8], breast [9,10] and stomach [11,12]. We asked: (1) Could blood be a non-sexual mode for the transmission of papillomavirus infections?…”
Section: Introductionmentioning
confidence: 99%
“…A strong causal relationship has been demonstrated between HPV and some types of cancers such as cervix uteri, penis, vulva, vagina, anus and oropharynx [4,6]. Controversial results have been obtained regarding the role of HPVs in esophagus [6][7][8], oral cavity [6,9], breast [10][11][12] and lung cancers [13,14]. In cervical lesions the HPV DNA is frequently found integrated into the host genome particularly in high grade cervical intraepithelial neoplasia and invasive cancer cases [15,16].…”
Section: Introductionmentioning
confidence: 99%